Three new species and a new key to the Diplonevra Lioy (Diptera: Phoridae) from Australia - Disney, R. H. L. (Zootaxa, 2011)
Diplonevra collessi sp. nov., D. fumosa sp. nov. and D. nigricorpus sp. nov. are described from Australia. A key to the eleven Australian species known in the male sex is provided.